Triple therapy with high-dose proton-pump inhibitor, amoxicillin, and doxycycline is useless for Helicobacter pylori eradication: a proof-of-concept study - Almeida, Nuno (2014)
Helicobacter pylori resistance to antibiotics is steadily increasing and multidrug-resistant strains are common and difficult to eliminate, mainly in countries where bismuth, tetracycline, furazolidone, and rifabutin are unavailable.